How to Stay A.L.I.V.E. in a World of Ever-Changing Technology: Keeping Up with Adult Learning in a Virtual Environment - Donna Mancuso; Dominique Chlup; Rochell McWhorter (Adult Education Research Conference, 2009)
The purpose of this paper is to discuss the benefits and barriers for adult learning within virtual environments.
Keywords: Virtual environments; technology; adult learning